The revitalization of Maqasid al-Mu‘amalat according to Abdullah bin Bayyah and Its implications on Islamic law (Research, Society and Development, 2021)
The revitalization of Islamic law continues to experience renewal in welcoming the new world economy era that offers the influence of global cultural acculturation and advances in information technology on the one hand, and the rise of spiritualism and nationalism on the other. The study of economics is not new in the discourse of Islamic law, which is better known as mu'amalat. For a long time, the discourse on the objectives of the Sharia (maqasid al-shari‘ah) has become a non-negotiable need. The necessity of knowing it, the urgency of studying it, and the implications of Muslim scholars’ thoughts in navigating the ocean of Islamic law to arrive at the sea of ​​wisdom are strongly influenced by maqasid al-shari‘ah. This is based on the assumption that it is not enough just to know and examine in detail the textual texts which can result in a misunderstanding of the purposes and objectives of God and His Messenger in formulating Islamic law, but it is very necessary to study the values and objectives of the Sharia texts that were revealed. Thus, Ibn Bayyah tried to combine the study of maqasid al-shari'ah with mu'amalat based on the objectives of the transaction and the results of observation of reality. In his research results, he stated that the revitalization of objectives of wealth as a new basis of thought in the discourse of Islamic law would update the concept of the jurisprudence of transactions in its old face which was rigid, out of date, conservative, and less applicable. This is like the human need for wealth considered as a crucial thing that occupies the first position in objectives of wealth (maqasid al-mu'amalat).